The Yeast GTPase Mtg2p Is Required for Mitochondrial Translation and Partially Suppresses an rRNA Methyltransferase Mutant, mrm2 - Datta, Kaustuv (The American Society for Cell Biology, 2005)
The assembly of ribosomes involves the coordinated processing and modification of rRNAs with the temporal association of ribosomal proteins. This process is regulated by assembly factors such as helicases, modifying enzymes, and GTPases. In contrast to the assembly of cytoplasmic ribosomes, there is a paucity of information concerning the role of assembly proteins in the biogenesis of mitochondrial ribosomes. In this study, we demonstrate that the Saccharomyces cerevisiae GTPase Mtg2p (Yhr168wp) is essential for mitochondrial ribosome function. Cells lacking MTG2 lose their mitochondrial DNA, giving rise to petite cells. In addition, cells expressing a temperature-sensitive mgt2-1 allele are defective in mitochondrial protein synthesis and contain lowered levels of mitochondrial ribosomal subunits. Significantly, elevated levels of Mtg2p partially suppress the thermosensitive loss of mitochondrial DNA in a 21S rRNA methyltransferase mutant, mrm2. We propose that Mtg2p is involved in mitochondrial ribosome biogenesis. Consistent with this role, we show that Mtg2p is peripherally localized to the mitochondrial inner membrane and associates with the 54S large ribosomal subunit in a salt-dependent manner.